2022
DOI: 10.1115/1.4052547
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Swirl Instability in a Vane-Type Separator With Tomographic Particle Image Velocimetry

Abstract: The separation efficiency of a vane-type separator is greatly affected by swirl instability. The separator consists of a swirling vane, a recovery vane and a main pipe. Driven by centrifugal force, the bubbly flow tends to develop into stratified flow with a continuous gas core floating in the central axis of the separator and facilitating the separation. Yet, the straight gas core can turn into a double helix under some circumstances for example if the pressure difference across the orifices of recovery vane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Given the relatively low efficiency of two phase simulation, a simpli- F I G U R E 2 2 The variation of axial velocity profiles during the transition process 84…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the relatively low efficiency of two phase simulation, a simpli- F I G U R E 2 2 The variation of axial velocity profiles during the transition process 84…”
Section: Discussionmentioning
confidence: 99%
“…By intercepting its cross section indicated in Figure 22, it can be found that the swirl stability is related to the sign of the axial velocity near the recovery vanes, and the negative axial velocity causes the swirl instability. 84 The results in Figures 20 and 22 show that the axial velocity distribution at the center of the cross section changes from V-to W-shape when the air core transits from unstable to stable.…”
Section: Mechanism Of Instabilitymentioning
confidence: 96%